Efficacy and safety of belimumab during maintenance therapy in patients with systemic lupus erythematosus. (28th December 2021) - Miyazaki, Yusuke; Nakayamada, Shingo; Sonomoto, Koshiro; Kawabe, Akio; Inoue, Yoshino; Okubo, Naoaki; Iwata, Shigeru; Hanami, Kentaro; Tanaka, Yoshiya
Abstract: Objectives: The efficacy of belimumab (BEL) during maintenance therapy in patients with SLE remains unclear in the real-life clinical setting. This study investigated the efficacy and safety of BEL in patients with SLE during maintenance therapy. Methods: In this retrospective observational study, maintenance therapy was defined as low-dose glucocorticoid (GC) therapy (prednisolone equivalent dose of ≤0.2 mg/kg/day) in patients with a Safety of Estrogens in Lupus Erythematosus National Assessment-SLE Disease Activity Index (SELENA-SLEDAI) score <10. Participants comprised patients with SLE on HCQ or MMF [standard-of-care (SoC) group: n = 103] and those on BEL plus SoC (BEL+SoC group: n = 100). Selection bias was minimized using propensity score-based inverse probability of treatment weighting (IPTW). GC dose trajectories were modelled using growth mixture modelling (GMM). The primary end point was GC dose at 52 weeks. Results: No significant difference was observed in patient characteristics between the two groups after IPTW adjustment. The BEL+SoC group exhibited a significant decrease in GC dose. GC dose at 52 weeks and relapse rate were significantly lower in the BEL+SoC group than in the SoC group. The proportion of patients in one of four groups defined by GMM for which GC dose was tapered to 0 mg within 52 weeks (GC tapering-discontinuation group) was significantly higher in the BEL+SoC group than in the SoC group. In the BEL+SoC group, low SELENA-SLEDAI score and low GC dose at baseline were associated with being GC dose-tapering discontinuation. Conclusion: The present study suggests that BEL is suitable for patients with SLE during maintenance therapy.